Implementation of Sharia Principles in Financing Micro, Small and Medium Enterprises in Rural Areas - Yuliana, Yuliana; Faisal , Faisal; Herinawati, Herinawati; Muhammad Rasyid, Laila (Fakultas Syariah Institut Agama Islam Negeri Lhokseumawe, 2025)
PT PNM Mekaar Syariah is an institution engaged in sharia financial services that provides financing in the form of capital to support business actors in developing their businesses. Even if the business fails, customers are still required to repay their loans. This study aims to determine the implementation, obstacles, and efforts in applying sharia principles to micro, small, and medium enterprise financing at PT PNM Mekaar Syariah Blang Mangat. This research is a qualitative study using a legal-empirical approach with a descriptive nature. The research data used are sourced from primary and secondary data. Primary data were obtained from observations and interviews, while secondary data were obtained from books, articles, and relevant scientific publications. The research data was systematically organized, beginning with data reduction, data presentation, and conclusion drawing. The research findings revealed that the implementation of Sharia principles and contracts by PT PNM Mekaar Syariah Blang Mangat Branch has not fully adopted Sharia principles, as evidenced by its operational practices not fully adhering to the murabahah system. The obstacles encountered by customers are that they often choose financing not for business purposes but for personal needs. This can lead to various challenges such as late payments, increased personal expenses, and difficulties in managing customer business operations. Efforts made include actively monitoring customers to detect potential late payments or defaults early on.